2011
DOI: 10.1039/c0em00791a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and organic matter on the partitioning of perfluoroalkyl acid (PFAs) to clay particles

Abstract: The influence of salinity and organic matter on the distribution coefficient (K(d)) for perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in a brackish water-clay system was studied. The distribution coefficients (K(d)) for PFAs onto inorganic clay surfaces increased with salinity, providing evidence for electrostatic interaction for the sorption of PFAs, whereas the relationship between K(d) and organic carbon content (f(oc)) suggested that hydrophobic interaction is the primary driving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(74 citation statements)
references
References 25 publications
6
67
0
1
Order By: Relevance
“…4) and the distribution map of Kd and ƒoc in the lake (Fig. 1) suggested that the organic carbon content dominated the distribution of PFOS in the sediment, which was consistent with earlier reported works where hydrophobic interactions played a strong role in the adsorption of long chain PFCs in the sediments (Jeon et al, 2011;Pan et al, 2009). …”
Section: Buffering Reservoir Of Pfos In the Sediment And Partition Ofsupporting
confidence: 78%
“…4) and the distribution map of Kd and ƒoc in the lake (Fig. 1) suggested that the organic carbon content dominated the distribution of PFOS in the sediment, which was consistent with earlier reported works where hydrophobic interactions played a strong role in the adsorption of long chain PFCs in the sediments (Jeon et al, 2011;Pan et al, 2009). …”
Section: Buffering Reservoir Of Pfos In the Sediment And Partition Ofsupporting
confidence: 78%
“…Because of salt intrusion, the north branch often had significantly higher salinity and suspended sediment concentrations than the south branch (Zhang et al, 2011). As previously discussed, the increase of Cr and Cd along the north branch should be ascribed to the release of the particle-bound phase into the water phase under the drive of the ''salt-out effect'' (Jeon et al, 2011).…”
Section: Spatial Distribution Of Heavy Metalsmentioning
confidence: 94%
“…where K D (L/kg) is the sediment-water distribution coefficient, C sediment is the concentration in sediment (mg/kg dry wt), and C water is the concentration in water (mg/L [6]. This difference may be caused by the difference in sediment composition and overall environmental parameters such pH and Ca 2þ , which are known to affect sorption of PFOS to sediment [10,15,[19][20][21][22][23]. Distribution coefficients were normalized to carbon content, using [6]; and higher than the 2.57 AE 0.13 from the laboratory experiment from Higgins and Luthy [15].…”
Section: Field-based Sediment-water Distribution Coefficientsmentioning
confidence: 99%